Objectification and resistance of women against patriarchal shackles in anime Haikara-san ga Tooru Movie 1: Benio, Hana no 17-sai - Noviana, Fajria; Avilla, Maria Teresa; Wibisono, Nabillah Azalia (Japanese Research on Linguistics, Literature, and Culture, 2023)
Objectification of women can be found in various media, including in literature, both classical and popular works. Therefore, this paper examines the objectification female characters experienced and their resistance to patriarchal culture in the anime Haikara-san ga Tooru Movie 1: Benio, Hana no 17-sai, which received the first Kodansha Manga Award. This study uses a feminist literary criticism approach that focuses on radical-liberal feminism. Data in conversations, actions, and events representing women's objectification and resistance to this treatment were collected using a note-taking technique. As a result, three treatments of objectification of women were found: arranged marriages, demands on women to be skilled in domestic tasks, and demeaning women. Meanwhile, women resist that objectification acts by rejecting arranged marriages, fighting against the demeaning of women, and working in the public sphere. From these findings, it is concluded that the objectification of women is constructed, consumed, and reproduced by men and women. Women, like men, should be treated as human beings with their rights, not as objects that can be traded, owned, or demeaned.